Biochar enhanced thermophilic anaerobic digestion of food waste: Focusing on biochar particle size, microbial community analysis and pilot-scale application. (1st April 2020) - Zhang, Le; Lim, Ee Yang; Loh, Kai-Chee; Ok, Yong Sik; Lee, Jonathan T.E.; Shen, Ye; Wang, Chi-Hwa; Dai, Yanjun; Tong, Yen Wah
Graphical abstract: Highlights: Thermophilic food waste digestion with varied particle size of biochar was examined. All examined biochars (<50 μm to 3 cm) significantly improved methane production. Bacteria Thermotogae and methanogens Methanothermobacter & Methanosarcina enriched. The synergy of hydrogenotrophic and acetoclastic methanogenic pathways was achieved. Both technical and economic feasibility of adding biochar strategy were validated. Abstract: Effectiveness of biochar addition to enhance thermophilic semi-continuous anaerobic digestion (AD) of food waste for methane production was investigated with a focus on dosage and particle size of biochar, pilot-scale application and elucidation of methanogenic pathways. Optimal dosage range of biochar was determined as 7.5 to 15 g per L working volume based on lab-scale batch AD. Effects of biochar with different particle sizes at a model dosage of 15 g/L were evaluated in a semi-continuous AD experiment, results of which showed that all the examined biochars with different particle sizes (<50 μm to 3 cm) substantially enhanced the average methane yields (0.465–0.543 L/gVS) compared to control digesters which failed due to overloading (≥3.04 gVS/L/d). No significant difference in methane yields, however, was observed among digesters with different particle sizes of biochars, except for 1–3 cm. The core reason for this phenomenon was that the biochars with different particle sizes had similar properties (e.g. density, surface area and pore size) and that the floating of large particle size (1–3 cm) of biochar with a density of 847 kg/m 3 was not conducive to microbial growth. Metagenomic analysis was performed to determine the predominant microbial species and to explain the main methanogenic pathways in biochar-amended digesters using 16S rRNA sequencing. In the biochar-amended digester, bacterial phylum Thermotogae containing a major genus of Defluviitoga was selectively enriched with gradual increase of organic loadings, while simultaneously enriched methanogen genera Methanothermobacter and Methanosarcina, which showed a synergy of hydrogenotrophic and acetoclastic methanogenic pathways, jointly enhanced the methane productivity. Both technical feasibility and economic feasibility of adding biochar with simple pretreatment (e.g. smash) were validated in the pilot-scale thermophilic semi-continuous AD operations.